A case series Of Shewanella algae bacteremia with different outcomes - Faisal, Ummu Salamah; Hamzah, Fatin Farahani; Zainulabid, Ummu Afeera; Chuan Hun, Ding (Elsevier, 2023)
Shewanella spp. is increasingly recognized as an emerging pathogen causing skin and soft tissue infection (SSTI). They are found ubiquitously in soil and the aquatic environment, particularly in warmer geographical climates. We present 2 cases of S. algae infection. The first case involves a 75- year-old man with underlying chronic lymphocytic leukaemia (CLL) who developed rapidly worsening left-hand cellulitis. S. algae was isolated from cultures of both his blood and right-hand swab. His antibiotics were revised from ampicillin-sulbactam to ceftazidime, and he recovered well after two weeks of intravenous ceftazidime. The second is a fatal case of septic shock due to leg cellulitis with S. algae bacteraemia. Unfortunately, this patient succumbed to his illness within 72 hours of hospital admission.